Massive Cellular Angiofibroma of the Vulva. Issue 3 (July 2017) - Santiago, Diana; Perlman, Barry; Lespinasse, Pierre; Chokshi, Ravi; Galan, Mark; Heller, Debra S.
Abstract : Cellular angiofibromas of the vulva are uncommon and usually small and circumscribed. A massive, infiltrative, cellular angiofibroma extending into the pelvis is described.